Evolution of lymph node staging in esophageal squamous cell carcinoma: insights from lymph node metastatic stations - Li, Kexun; Lu, Simiao; Mao, Jie; Han, Yongtao; Peng, Lin; Leng, Xuefeng (Frontiers in Oncology, 2025)
Esophageal squamous cell carcinoma (ESCC) is a globally prevalent malignancy with distinct regional variations, particularly concentrated in East Asia, including China and Japan. The Union for International Cancer Control/American Joint Committee on Cancer (UICC/AJCC) system offers simplicity but lacks emphasis on anatomical specificity, such as upper mediastinal metastases. Conversely, the Japan Esophageal Society (JES) system provides detailed regional stratification, aiding preoperative planning and tailored therapy, though it demands greater clinical expertise. This review evaluates the current state of pathological lymph node staging systems for ESCC, comparing the UICC/AJCC and JES approaches and exploring emerging trends in China toward station-based staging.